2019
DOI: 10.3988/jcn.2019.15.1.46
|View full text |Cite
|
Sign up to set email alerts
|

White-Matter Hyperintensities and Lacunar Infarcts Are Associated with an Increased Risk of Alzheimer's Disease in the Elderly in China

Abstract: Background and PurposeThis study investigated the contribution of white-matter hyperintensities (WMH) and lacunar infarcts (LI) to the risk of Alzheimer's disease (AD) in an elderly cohort in China.MethodsOlder adults who were initially cognitively normal were examined with MRI at baseline, and followed for 5 years. WMH were classified as mild, moderate, or severe, and LI were classified into a few LI (1 to 3) or many LI (≥4). Cognitive function was assessed using the Mini Mental State Examination and the Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
10
0
2
Order By: Relevance
“…When multiple markers of CSVD are present at the same time, they may have synergistic or superimposed effects on cognitive dysfunction ( Jokinen et al, 2012 ; Ye et al, 2019 ). The underlying mechanism of CSVD leading to cognitive impairment is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…When multiple markers of CSVD are present at the same time, they may have synergistic or superimposed effects on cognitive dysfunction ( Jokinen et al, 2012 ; Ye et al, 2019 ). The underlying mechanism of CSVD leading to cognitive impairment is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…From June 1, 2020, to December 31, 2021, patients diagnosed with AD at the rehabilitation department or neurology department of the Chongqing Daping Hospital were recruited to participate in our study. AD was diagnosed by a senior neurologist following a previously described protocol [14]. All patients participating in the study underwent MRI examination.…”
Section: Subjectsmentioning
confidence: 99%
“…WMH has been widely accepted in imaging associations with aging and AD (Chen et al, 2011). For example, a longitudinal study showed that a high burden of WMH was associated with an increased risk of developing AD over a 5-year follow-up period (Ye et al, 2019). One cohort study showed that overall WMH load was associated with AD risk factors in subjects whose cognitive function was not impaired.…”
Section: Alzheimer's Diseasementioning
confidence: 99%